(untitled) (Revista de Medicina Clinica, 2021)
Background Barotrauma in mechanical ventilation is defined as lung damage attributable to the application of high airway pressure. In patients with COVID-19, the incidence of this complication is more common than in other ARDS patients. The aim of this study was to determine the risk factors for developing barotrauma in patients under MV with COVID-19 associated ARDS. Secondary objectives were to determine the incidence of barotrauma and its association with mortality. Patients and Methods. A case-control nested in a cohort study was performed in patients with diagnosis of SARS-COV2 infection and mechanical ventilation, admitted in a Hospital in Mexico City from April 2020 to January 2021. Cases were defined as patients with barotrauma and controls were selected from a random sample of a COVID-19/ARDS cohort. Demographic, ventilatory and clinical variables were analyzed. Prognostic univariate and multivariate modeling were carried out through logistic regression. Results. A total of 267 patients were included in the cohort, 15 patients developed barotrauma (5.6%) and 252 patients were randomized/matched as controls. Significant differences between groups in ventilatory parameters such as PEEP (13±2 cmH2O vs. 11±3 cmH2O, p=.04), tidal volume (431±49 mL vs 452±57 mL, p=0.05), PaO2 (52±13mmHg vs. 62±15mmHg, p=0.05), and the PaO2/FiO2 ratio (56±18 vs. 66±16, p=0.05) were found. The resulting prognostic risk factors were smoking history, PEEP, Hypotension, non-ICU hospitalization and SOFA-score, with a value of r2=0.78, AUC of 0.82. Conclusions. This case control study provides insights on the risk factors for COVID-19/ARDS barotrauma development; smoking history, higher PEEP, hypotension, and non-ICU hospitalization.